Electrophysiological Correlates of Processing Warning Signs With Different Background Colors: An Event-Related Potentials Investigation - Yuan, Jingpeng; Song, Zhipeng; Hu, Ying; Fu, Huijian; Liu, Xiao; Bian, Jun (Frontiers in Psychology, 2021)
Warning signs, as a type of safety signs, are widely applied in our daily lives to informing people about potential hazards and prompting safe behavior. Although previous studies have paid attention to the color of warning signs, they are mostly based on surveys and behavioral experiments. The neural substrates underlying the perception of warning signs with different background colors remain not clearly characterized. Therefore, this research is intended to address this gap with event-related potentials technique. Warning signs with three different background colors (i.e., white, yellow and blue) were used in the experiment. The results showed that the perceptual differences between different warning signs were present in the form of differential event-related potentials components (P1, N1, P2, N2 and P3) though subjects were not required to explicitly attend to the warning signs.